Percepção dos alunos no ensino básico sobre as mulheres na ciência: pesquisa e proposta de intervenção - Modesto, Estela Rafaldine (Universidade Federal de São Carlos, 2024)
The presence of women in the academic world has been fraught with difficulties throughout the history of science. Even though they are gradually conquering their space, there is still a great deal of differentiation between men and women, such as the segregation of areas of knowledge considered feminine and masculine. One of the causes of this issue is the presence of stereotypes about the image of the scientist, who is often seen as a man, wearing a lab coat, with messy hair, dark circles under his eyes, crazy, among other adjectives. In this context, this study aims to map the perceptions, classified by age and gender, of students aged between 8 and 17 about scientists and the presence of women in science and to propose an intervention through the production of a podcast. The activity was divided into two stages. First, the students were given a questionnaire and took the "Draw a Scientist" (DAST) test in order to understand their preconceptions about scientists. In the second stage, the students discussed the presence of women in science, using another questionnaire and the presentation of educational videos about female scientists. With this information, they discussed their perceptions and hypotheses about the reasons for not knowing about women scientists, as well as the difficulties of being a woman in science. In order to spread the word about women in science, a podcast was produced. The results showed that the students had the same stereotypical ideologies about scientists as those reported in the literature and initially believed that the invisibility of women in science was their own choice. During the discussion, the younger students showed a certain immaturity and did not understand the importance of the debate, but the girls (of all ages) and the older students showed concern and anger about the issue. In conclusion, the work achieved its objective by investigating students' perceptions of scientists and introducing them to women in science, with the difficulties they face. In addition, the proposed intervention through the podcast allowed us to go beyond the scope of research and advance scientific dissemination, as well as contributing to a critical-citizen education.
Perceptions of elementary school students about women in science: research and intervention
Keywords: Mulheres na Ciência; DAST; Ensino de Química; Podcast; Women in Science; Chemistry Teaching; CIENCIAS EXATAS E DA TERRA::QUIMICA